What are the current indications for use of radiofrequency devices in hip arthroscopy? A systematic review - Suarez-Ahedo, Carlos (J Hip Preserv Surg, 2015)
The role of radiofrequency energy (RFE) devices has been minimally studied in hip arthroscopy. The purpose of this study was to determine the role of RFE devices in hip arthroscopy through a systematic review of the literature. We searched the PubMed database using the following Medical Subject Heading terms: hip arthroscopy, hip radiofrequency, thermal capsulorrhaphy, thermal chondroplasty and radiofrequency debridement. Two authors independently reviewed the literature and included articles based on predetermined inclusion criteria. We excluded review, technique and experimental articles. After title and abstract review, we selected 293 articles for full-text review. Ten articles met the inclusion and exclusion criteria. For the included articles, a total of 305 hips underwent arthroscopy with concomitant RFE treatment at a mean age of 25.7 years. Eight articles presented patient-reported outcome (PRO) instruments, one study did not report an outcome instrument but utilized an evaluation of postoperative range of motion (ROM) and 1 year magnetic resonance image (MRI) and computed tomography (CT) imaging. The remaining article measured only the ROM pre- and postoperatively. Only one of the articles reviewed reported complications. Current evidence on the safety and indications for use of RFE devices in hip arthroscopy is insufficient. The literature shows mixed results regarding its use in hip arthroscopy. Although the use of thermal energy is not without risk, if used judiciously and appropriate precautions are taken to avoid damage to adjacent tissues, those devices can be useful for the treatment of certain intra-articular hip pathologies arthroscopically.